A Strategic Action Plan to Advance Circular Economy Practices in the Automotive Industry Based on Sector Insights to Support Sustainable Development - Pérez-Canto, Salvador; Ramos Garcia, Alvaro; De-las-Heras-Rosas, Carlos Javier (Wiley, 2026)
The circular economy is gaining traction as a transformative approach to address climate change and the shortcomings of the linear economic model, which is defined by unsustainable production and consumption patterns. This study explores the implementation of circularity principles in the Spanish automotive industry, with particular attention to the sector's ongoing transition toward sustainability in alignment with the United Nations Sustainable Development Goals and broader sustainable development objectives. The evolution of electric vehicles exemplifies this shift, underscoring the need to redesign production systems and manage resources more efficiently. Using a survey-based methodology complemented by expert panel input, and applying Principal Component Analysis, the research identifies critical challenges such as resource consumption, eco-design, technology development, and waste generation. The findings reveal a pressing need for a comprehensive green transition, highlighting specific deficiencies that require targeted action. To address these gaps, the study proposes a strategic action plan rooted in the principles of circularity, offering guidance for industry stakeholders and policymakers to accelerate the adoption of sustainable practices and foster long-term resilience in the automotive value chain
Keywords: Cambios climáticos; Economía circular; Automotive industry; Circular economy; Principal component analysis; Strategic action plan; Sustainable development